The use of action research as an appropriate method of introducing and evaluating change in nursing care in an accident & emergency unit in Durban - Part 2 - D. Kerr (AOSIS, 1996)
This 2-part article discussed firstly in Curationis 19.3 this year, the general characteristics of action research, compares several strategies of approach and describes the author's chosen method of applying action research to particular aspects of nursing care in an Accident & Emergency Unit in a Durban hospital. This second part describes identification of problems within the unit, the implementation of change and the limitations and potential of such study to nursing practice.